PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN BERBASIS CANVA UNTUK MENINGKATKAN PENGETAHUAN GURU SDN MEKARSARI 02 CIMANGGIS, DEPOK, JAWA BARAT - Zulherman, Zulherman; Hanifah May Wisuda Ashari, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Education requires technology to improve its quality. One of the uses of technology in education is to support learning. The purpose of the activity is to provide knowledge to teachers by utilizing the Canva application as a creative and innovative learning medium. The training method is by providing material as a basis for initial knowledge, an explanation of the use of the Canva application in learning and tutorials for making learning videos. The results of the activities of the participants were very active and enthusiastic in participating in the activities. The conclusion of the activity was continued for the development of learning media materials and contents.